2007
DOI: 10.1007/s00381-007-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate termination of life of newborns with spina bifida, a critical reappraisal

Abstract: Objects Deliberate termination of life of newborns (involuntary euthanasia) with meningomyelocele

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Although the exact definition of ‘hopeless and unbearable suffering’ is unspecified, we infer it to mean acute and chronic pain that is not alleviated by modern therapeutics. In fact, whether infants with open MMC actually experience an unbearable degree of pain is itself a matter of debate [4,15]. The evidence is sparse, and no rigorous studies evaluating patients using the many available neonatal and infant pain scales have been published.…”
Section: The Protocol: An Evidence-based Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Although the exact definition of ‘hopeless and unbearable suffering’ is unspecified, we infer it to mean acute and chronic pain that is not alleviated by modern therapeutics. In fact, whether infants with open MMC actually experience an unbearable degree of pain is itself a matter of debate [4,15]. The evidence is sparse, and no rigorous studies evaluating patients using the many available neonatal and infant pain scales have been published.…”
Section: The Protocol: An Evidence-based Analysismentioning
confidence: 99%
“…It has even been suggested that the practices drawn up in the GP are a violation of numerous articles of the United Nations Universal Declaration of Human Rights, such as those including the right to life, as well as the rights of nondiscrimination and the right to equal protection by the law [4]. …”
Section: The Protocol: An Ethical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Esses trabalhos afirmavam categoricamente que o protocolo era inaceitável e que ia frontalmente contra toda a noção de dignidade humana que fundamentou o ideário de direitos humanos de nossa civilização [26][27][28][29] .…”
unclassified
“…20 de Jong 21 cites that editorial in his critique of the Groningen Protocol, which permits the euthanasia of newborns with myelomeningocele in the Netherlands. According to de Jong, 21 the Protocol' s application to myelomeningocele is based on outdated and, in some cases, false information about the condition, leading to overly pessimistic assessments in most cases. Newly diagnosed parents participating in online forums, such as BabyCenter, routinely report being pressured to abort by obstetricians or maternal/fetal medicine specialists who present the "worst case scenario" but call it a "prognosis."…”
mentioning
confidence: 99%